An Evolutionary Perspective of the Lipocalin Protein Family - Diez-Hermano, Sergio; Ganfornina, Maria D.; Skerra, Arne; Gutiérrez, Gabriel; Sanchez, Diego (Frontiers in Physiology, 2021)
The protein family of Lipocalins is ubiquitously present throughout the tree of life, with the exception of the phylum Archaea. Phylogenetic relationships of chordate Lipocalins have been proposed in the past based on protein sequence similarities, but their highly divergent primary structure and a shortage of experimental annotations in genome projects have precluded a well-supported hypothesis for their evolution. In this work we propose a novel topology for the phylogenetic tree of chordate Lipocalins, inferred from multiple amino acid sequence alignments. Sixteen jawed vertebrates with fair coverage by genomic sequencing were compared. The selected species span an evolutionary range of 400 million years, allowing for a balanced representation of all major vertebrate clades. A consensus phylogenetic tree is proposed following a comparison of sequence-based maximum-likelihood trees and protein structure dendrograms. This new phylogeny suggests an APOD-like common ancestor in early chordates, which gave rise, via whole-genome or tandem duplications, to the six Lipocalins currently present in fish (APOD, RBP4, PTGDS, AMBP, C8G and APOM). Further gene duplications of APOM and PTGDS resulted in the altogether fifteen Lipocalins found in contemporary mammals. Insights into the functional impact of relevant amino acid residues in early diverging Lipocalins are also discussed. These results should foster the experimental exploration of novel functions alongside the identification of new members of the Lipocalin family.